GAMIFICATION AS A TOOL FOR INCREASING THE EFFICIENCY OF PROFESSIONAL TRAINING IN HIGHER EDUCATION - Kondur, Oksana (Mountain School of Ukrainian Carpaty, 2022)
The article is devoted to issues of improving the effectiveness of the process of studying mathematics methods in higher education with the help of game technologies. An educational game is a joint activity, which is one of the important psychological and pedagogical foundations of the process of self-realization of an education seeker in educational activities. Game methods are interactive learning methods. They are practice-oriented, aimed at activating students, contribute to their professional development and, accordingly, increase the quality of educational activities and the effectiveness of professional training. This determines the relevance of the application of game technologies in the educational process of a higher school. The article analyzes various classifications of game technologies in education. It is justified that the main didactic goals of the educational game can be achieved if it is carefully prepared from the organizational and methodological side. The possibilities of using situational game learning technologies for the development of professional competence of future teachers are described. Thanks to an organized pedagogical experiment, it was established that game technologies for teaching mathematics and mathematics methods contribute to the creation of an active, business-like, emotional educational environment. They help students develop communication skills. They also contribute to a deeper understanding of mathematical and methodical definitions. The role of the teacher and his interaction with students at various stages of the application of game technologies are analyzed. His positional place during the game is characterized. Modern requirements for the professional training of specialists in institutions of higher education lead to the permanent implementation of innovative learning technologies, among which game technologies occupy an important place. Gamification of the educational process in higher education improves the preparation of students for future professional activities in society.